Bullying entre crianças e adolescentes: a questão dos direitos humanos e dos conflitos escolares - Sena, Michel Canuto de (2022)
Bullying can be characterized as a social issue, which generates social, sentimental, family and health impacts on children and adolescents. In this sense, the present study has as its theme Bullying among children and adolescents in Campo Grande, Mato Grosso do Sul. Bullying commonly occurs in a school environment, involving the aggressor, the victim and the public, which are usually students from the school itself. Unfortunately, this type of violence can cause irreparable harm to the victim. In addition to the violation of human rights, such as the dignity of the human person. The main objective of this study is to identify bullying among children and adolescents from public schools in Campo Grande, Mato Grosso do Sul. The study is justified by the need to explore and understand bullying in a school environment in the region of Mato Grosso do Sul. the methodology is presented as a study with a quantitative, exploratory, descriptive and transversal approach. The research participants were teachers from two municipal public schools, from the sixth to the ninth grade. Data collection was carried out through an online questionnaire about the occurrence of bullying at school, made available to teachers through google forms. As a result, it was found that 81.3% responded that they sometimes perceive threats or insults received by students in the school environment, while 15.6% perceive this act many times. Still, 69.7% realized that bullying sometimes occurs among students, while 30.3% of teachers surveyed responded that they often perceive this violent act in the school environment. It is concluded that the data obtained through the questionnaire allowed us to understand the phenomenon of bullying among children and adolescents, as well as to identify the role of the school in relation to cases of bullying. Also: (I) there is the occurrence of bullying; (II) the school in many cases does not know how to identify cases that are considered bullying or not; (III) The school offers assistance and follow-up in cases of bullying. The data show that bullying occurs in a school environment, teachers most of the time perceive the occurrence, but do not know or do not carry out more practical actions that can save the lives of children and adolescents.